2000
DOI: 10.1021/jp000946v
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Study of the FeCl3-Doped Dimer of Polyaniline; A Good Model Compound of Emeraldine Salt

Abstract: In this paper, optical and vibrational properties of the FeCl 3 -doped dimer of polyaniline, a model compound of emeraldine salt are presented. This oligomer is synthesized according to the method reported by Zaghal et al.. A complete assignment of the fundamental in-plane Raman and infrared modes (1700-600 cm -1 ) of this oligoaniline is proposed. The observed frequencies of the dark blue microcrystals are compared with those acquired by vibrational calculations based on a valence force field model. To show, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 52 publications
6
113
0
3
Order By: Relevance
“…A new sharp band of medium-to-strong intensity at 1041 cm -1 is observed in the spectrum of Ac-B, which can be attributed to the S=O stretching in sulfonate SO 3 -group substituting the aromatic ring [8][9][10]. The bands observed at 760 and 695 cm -1 in the spectrum of Ac-B (at 753 and 688 cm -1 for Ac) correspond to the C-H out-of-plane bending and the ring out-of-plane deformation of monosubstituted phenylene ring, respectively [8,32,33,35,41,50]. Increased intensity of the band at 695 cm -1 in the spectrum of Ac-B, in comparison to the weak band at the same position in the spectrum of H-B, indicates a higher content of aniline oligomers bearing monosubstituted phenyl rings as terminal units and/or more pronounced branching of the chains in the nanotubular sample prepared in acetic acid in comparison to the sample H. The spectra of the samples Su-B and W-B are nearly identical with the spectrum of sample Ac-B, all samples being prepared in mildly acidic media.…”
Section: Granular Pani Samples H and H-bmentioning
confidence: 95%
See 1 more Smart Citation
“…A new sharp band of medium-to-strong intensity at 1041 cm -1 is observed in the spectrum of Ac-B, which can be attributed to the S=O stretching in sulfonate SO 3 -group substituting the aromatic ring [8][9][10]. The bands observed at 760 and 695 cm -1 in the spectrum of Ac-B (at 753 and 688 cm -1 for Ac) correspond to the C-H out-of-plane bending and the ring out-of-plane deformation of monosubstituted phenylene ring, respectively [8,32,33,35,41,50]. Increased intensity of the band at 695 cm -1 in the spectrum of Ac-B, in comparison to the weak band at the same position in the spectrum of H-B, indicates a higher content of aniline oligomers bearing monosubstituted phenyl rings as terminal units and/or more pronounced branching of the chains in the nanotubular sample prepared in acetic acid in comparison to the sample H. The spectra of the samples Su-B and W-B are nearly identical with the spectrum of sample Ac-B, all samples being prepared in mildly acidic media.…”
Section: Granular Pani Samples H and H-bmentioning
confidence: 95%
“…This band is weaker in the spectrum of the corresponding base H-B and corresponds to the C-N stretching vibration of a secondary aromatic amine [23,40]. The band characteristic of the conducting protonated form is observed at 1248 cm -1 in the spectrum of sample H. It has been interpreted as corresponding to a C-N +• stretching vibration in the polaron structure [41]. The spectrum of the sample H exhibits a strong and broad band centered at 1148 cm -1 , which has been assigned to the vibration mode of the -NH + = structure, and is associated with the vibrations of the charged polymer units Q=NH + −B or B−NH +• −B [23,32,40].…”
Section: Granular Pani Samples H and H-bmentioning
confidence: 99%
“…Above 800 ∘ C all these materials, interestingly, result in complete degradation (i.e., nearly zero mass) which indicates the formation of metalfree NDC by this process. In contrast, most of the processes pertain to carbonaceous material preparation; incorporation of metal impurities is implicit [31]. 3+/2+ that has very minimal surface dependence on particular surface sites or functional groups is also employed as the redox system for activity assessment.…”
Section: Thermal Stability Analysismentioning
confidence: 99%
“…For other NDCs, the peak-to-peak separation is observed in between 100 and 150 mV and cathodic/anodic peak current ratios ( a / c ) are close to one. It is reported that the introduction of nitrogen heteroatom in the carbon structure improves the electroactivity of the materials since the nitrogen containing lone pair of electrons undergoes delocalization within the carbon material [31][32][33][34]. This lone pair of electrons is responsible for the enhanced electrochemical activity of the NDCs.…”
Section: Cyclic Voltammetricmentioning
confidence: 99%
“…Observa-se na Figura 58 que os nanotubos formados apresentam estrutura morfológica bem mais definida sem a presença de uma grande quantidade de estruturas granulares entre os mesmos. [199][200][201][202].…”
Section: Síntese E Caracterização Morfológicaunclassified